Educational Burnout and Its Relation with Mental Health in Birjand university of medical sciences Students - Tahereh Khazaee; Mahmood Reza Tavakkoli; Mandana Jaberi darmiyan; Mitra Yaghoobi poore (Babol University of Medical Sciences, 2015)
ABSTRACT BACKGROUND AND OBJECTIVE: Due to various factors, college education is a stressful period and the students may experience educational burnout for different reasons such as demanding high level of endeavor for learning or lack of supportive mechanisms for effective coping with the problems. METHODS: In this correlation type cross - sectional study, 200 paramedic students were selected through randomized stratified sampling with standardized educational burnout and mental health questionnaires. The obtained data were analyzed by SPSS software (v: 11.5), T test, Chi square, and correlation statistical tests. FINDINGS: Mean age of the students was 21.67±1.4 years, mean educational burnout score 40.56±8.5 and mean mental health score 28.03±11.2. Mean educational burnout score in lab technology students and anesthesia students were higher in comparison with radiology and operation room students. However, there is no statistically significant difference. It was found that there was a statistically significant association between the students' educational burnout score and mental health score (p<0.05). CONCLUSION: According to the given results, it can be concluded that some fields in the college education can cause educational burnout and therefore have negative impact on mental health of the students.